Filipino Spirituality of the Cross and Suffering: Healing and Re-Traumatization Among Natural Disaster Victims - Josuah Macalos De Rosas (Sekolah Tinggi Teologi Abdiel, 2026)
In 2024, the World Risk Report ranked the Philippines among the nations which is most vulnerable to natural disasters. The country regularly endures typhoons, earthquakes, volcanic eruptions, and climate-related disruptions. At the same time, it remains deeply religious, with about ninety percent of Filipinos identifying as Christian. In this context, spirituality shapes how communities interpret trauma and sustain hope. This article examines the Filipino spirituality of the cross and suffering as a framework for resilience. Devotion to the suffering Christ, expressed in Holy Week rituals and popular processions, forms both personal piety and communal solidarity across Catholic and Protestant communities. While many studies emphasize the positive effects of religiosity on disaster survivors, few critically assess how certain doctrines and practices may retraumatize victims, especially when disasters are interpreted as divine punishment. The article demonstrates that in the different stages of disaster: devastation, disillusionment, reform, and wisdom, a pastoral and liturgical responses specifically in the stages of reform and wisdom, are necessary intervening factors of changing the worldviews and beliefs about disasters from the perspectives of the disaster victims.